ANALISIS SISTEM JARINGAN IRIGASI BENDUNGAN PONTAK KABUPATEN BOLAANG MONGONDOW UTARA DENGAN SISTEM INFORMASI GEOGRAFIS - Haiqal B. Rivai; David P. Rumambi; Sandra E. Pakasi (COCOS, 2021)
ABSTRACTThe purpose of this study is to analyze the irrigation network system of the PontakDam, North Bolaang Mongondow Regency based on geographic information systems. Themethod used in this research is the method of spatial analysis, namely a field survey by takingseveral measurements whose data is presented in the form of maps, tables and analyzeddescriptively. Information on the irrigation network of the Pontak dam has been presented ina spatial form in the form of a map of the irrigation network of the Pontak dam. The area ofPontak right irrigation network service is 131.63 Ha. If referring to the data from the PUPRService in the field of water resources, North Bolaang Mongondow Regency regarding thearea of rice fields in 2019 of 136.84 Ha, there is a difference in the area of rice fields of 5.21Ha. The index of the physical condition of the Pontak dam irrigation network is 93.44% witha weight of 42.05 infrastructure from a maximum value of 45.00, so routine maintenance isneeded.Keywords : Irrigation Network System, Geographic Information System